Effect of acetylstrophanthidin on action potential duration and relation with extracellular potassium in sheep isolated Purkinje fibers - Xie Jing-Tian; Chen Wei; Cunningham Peter M; January Craig T (Acta Pharmacologica Sinica, 2016)
AIM: To study the relation between the effect of acetylstrophanthidin on action potential duration (APD) and the extracellular potassium concentration. METHODS: Effect of acetylstrophanthidin (AS 0.15 mmol.L-1) on APD at different extracellular potassium concentrations was studied at the stimulation cycle lengths of 990 and 690 ms in sheep isolated cardiac Purkinje fibers using the standard microelectrode technique. RESULTS: At [K+]o 4.0 mmol.L-1, the biphasic effect of AS on APD appeared obviously. Both APD50 and APD90 were lengthened within the first 10 min of drug exposure. After 10 min, they were shortened at all pacing cycle lengths. On the other hand, at [K+]o 5.4 mmol.L-1, AS only shortened APD markedly without lengthening effect on it. The biphasic and monophasic effects of AS on APD were found at [K+]o 4.0 mmol.L-1 and 5.4 mmol.L-1, respectively. CONCLUSION: The effect of AS on APD was related to the concentration of [K+]o.